2017
DOI: 10.18176/jiaci.0174
|View full text |Cite
|
Sign up to set email alerts
|

The Biomarker Salivary SP-D May Indicate Small Airway Inflammation and Asthma Exacerbation

Abstract: Background: Noninvasive and child-friendly biomarkers are important tools for understanding the various phenotypes of childhood asthma. Objective: The aim of this study was to examine the usefulness of salivary surfactant protein (SP) D in assessing the pathophysiology of childhood asthma. Methods: We measured salivary concentrations of SP-D and forced oscillation technique (FOT) indexes in 19 healthy controls and 21 asthmatic children. Regression equations for the predictive values of FOT indexes were generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recent studies have supported these initial observations and demonstrated that sputum SP-D is increased in severe asthma or severity of exacerbation ( 338 , 339 ), that serum SP-D increases stepwise in mild to moderate and severe disease, and correlates inversely with lung function and directly with small airway resistance ( 273 ). Mackay et al ( 19 ) demonstrated that serum SP-D was increased in severe asthma with mixed eosinophilic and neutrophilic inflammation and enriched for SP-D breakdown products.…”
Section: The Role Of Sp-d In Respiratory Diseasementioning
confidence: 86%
“…Recent studies have supported these initial observations and demonstrated that sputum SP-D is increased in severe asthma or severity of exacerbation ( 338 , 339 ), that serum SP-D increases stepwise in mild to moderate and severe disease, and correlates inversely with lung function and directly with small airway resistance ( 273 ). Mackay et al ( 19 ) demonstrated that serum SP-D was increased in severe asthma with mixed eosinophilic and neutrophilic inflammation and enriched for SP-D breakdown products.…”
Section: The Role Of Sp-d In Respiratory Diseasementioning
confidence: 86%
“…A strong correlation between symptom control and salivary levels of eotaxin, IL-5 and IL-8 was reported in both children and adults with asthma [ 38 ]. Another study assessed salivary surfactant protein D (SP-D) levels [ 66 ], known to be secreted from the salivary glands, as well as from type II alveolar epithelial cells and nonciliated Clara cells [ 67 ]. They observed that elevated SP-D may reflect asthmatic inflammation in peripheral small airways and the risk of losing asthma control.…”
Section: Biomarkersmentioning
confidence: 99%
“…They observed that elevated SP-D may reflect asthmatic inflammation in peripheral small airways and the risk of losing asthma control. Authors indeed found a correlation of SP-D levels with both the increased resistance of peripheral airway measured with forced oscillation technique and the clinical severity of asthma exacerbations [ 66 ]. A recent comparative proteomic analysis between healthy and asthmatic groups, despite performed on small population sample, identified significant modifications in salivary proteins using gel-based quantitative proteomics.…”
Section: Biomarkersmentioning
confidence: 99%
“…They found that salivary SP-D levels are increased in asthmatic children. They commented that salivary SP-D may reflect asthmatic inflammation in peripheral small airways and may be a useful marker for monitoring the degree of exacerbation in childhood asthma [ 121 ]. This is in contrast to earlier findings, in which SP-D levels in BAL fluids were lower in adults with severe asthma [ 122 ].…”
Section: Proteomics Approaches In Respiratory Allergymentioning
confidence: 99%